Strengthening of prism beam by using NSM technique with roots planted in concrete - Hassen, Douread R.; Abdul Samad, Abdul Aziz; A. Azeez, Alyaa (Science Publishing Corporation, 2017)
This paper presents experimental results of four prismatic concrete reinforced beam and strengthened by NSM (Near surface mounted) FRP (Fiber Reinforced Polymer) reinforced technique, with additional roots planted in the concrete. The strengthening technique causes load capacity of beams to increase from (6%-8%).A decrease in mid-span deflection was also observed from (4%-5%).Using this technique gave increasing in flexural beam resistant under the same conditions and this increasing was also noted in shear beam resistant.